Exploring the Landscape: Challenges and Opportunities in Islamic Education Technology - Elihami Elihami; Muwafiq Ibrahim Mas’ud; Abdi Darmawan (Jurnal Pendidikan Progresif, 2024)
Exploring the Landscape: Challenges and Opportunities in Islamic Education Technology. Objective: Islamic education is on the brink of transformation with the integration of artificial intelligence (AI). This research explores AI's potential in Islamic education, focusing on its benefits, challenges, and ethical considerations.Method: A mixed-methods approach was utilized, combining literature review, case studies, and expert consultations. Quantitative analysis of student performance metrics was integrated with qualitative insights from stakeholders to offer a comprehensive view of AI's impact. Findings: AI has the potential to revolutionize Islamic education by enabling personalized learning experiences, improving accessibility, and streamlining administrative processes. It can adapt to various learning styles, enhance student engagement, and support diverse educational needs. However, challenges such as ensuring accuracy, managing biases, and ethical concerns must be addressed for effective integration. Conclusion: AI offers significant opportunities to advance Islamic education, but its implementation must be approached with careful consideration of ethical issues and alignment with Islamic values. This research provides valuable insights for educators, policymakers, and technology developers on leveraging AI to enrich Islamic education while addressing potential challenges. Keywords: education, artificial intelligence, islamic education, education, islamic.DOI: http://dx.doi.org/10.23960/jpp.v14.i2.202478